Fluorine ion-implanted polystyrene improves growth and viability of vascular smooth muscle cells in culture - Bacáková, L; Mares, V; Bottone, M G; Pellicciari, C; Lisá, V; Svorcík, V (Journal of biomedical materials research, 2000)
Vascular smooth muscle cells derived from the rat aorta were cultured on unmodified or F(+) ion-implanted polystyrene (5 x 10(12) or 5 x 10(14) ions/cm(2), energy 150 keV). In 1-day-old cultures, the cells adhered to the modified polystyrene in higher numbers and over larger contact areas. Increased resistance of the cells to trypsin-mediated detachment from the growth support indicated an improved adhesion of cells to the modified polymer at later culture intervals. The cells cultured on ion-modified polymers also were larger and had a higher total protein content. By use of immunocytochemistry, several specific protein species were increased, including the cytoskeletal alpha-actin and vimentin and the plasma membrane-associated vinculin, talin, alpha-v integrins, ICAM-1, and VCAM-1, which account for stronger cell-cell and cell-extracellular matrix adhesion. The lower number of cells found floating in the medium suggests that the spontaneous detachment of cells from the modified polystyrene was lower and that the viability of the adhered cell population was higher. As was shown by the two-parameter flow-cytometric measurements of BrdU incorporation and DNA content, as well as by (3)H-thymidine autoradiography, the cell proliferation on samples modified by the dose of 5 x 10(12) ions/cm(2) was similar to that in controls; and at the dose of 5 x 10(14) ions/cm(2), it tended to be even lower. The cells grown on the polymer implanted with the dose of 5 x 10(12) ions/cm(2) responded to a new artificially created cell-free area in a confluent cell layer by more intense migration whereas at the dose of 5 x 10(14) ions/cm(2), the migration ability of cells was similar to that on the unmodified polymer. The data revealed a higher biocompatibility of ion-implanted polystyrene with vascular smooth muscle cells in culture. There was better adhesion, differentiation, and survival, and there was neither excessive migration nor proliferation.
Keywords: Biocompatible Materials; kultivované buňky; Rats; Cell Adhesion; Cell Differentiation; Polystyrenes; DNA; fluor; proteiny; Cell Adhesion Molecules; povrchové vlastnosti; buněčné dělení; biokompatibilní materiály; Cell Division; Cell Size; krysa rodu Rattus; velikost buňky; svaly hladké cévní; Muscle, Smooth, Vascular; Cells, Cultured; Surface Properties; zvířata; Cytoskeletal Proteins; cytoskeletální proteiny; viabilita buněk; Cell Survival; Fluorine; buněčná adheze; buněčná diferenciace; testování materiálů; Materials Testing; molekuly buněčné adheze; Proteins; polystyreny; Animals